Sonata n.2 para violoncelo e piano (1912) de Glauco Velasquez: estudo interpretativo e tratamento editorial da obra - Marie Stephanie Jeanne Bernard (2012)
Because it is a work relevant to the cello repertoire and not be made available to the artistic community, a sonata for cello and piano no. 2 of Glauco Velasquez was selected by the author as an object of study. It is proposed to interpretative analysis of the work and the editing of manuscripts of the composer, with suggestions for performance and recording DVD as the final result of the research. It is also intended through this study, to recognize the work of Glauco Velasquez inside the Brazilian cultural heritage.The methodology includes (1) a brief account of musical history in Rio de Janeiro at the time of Glauco Velasquez, (2) concise biography of the composer, (3) interpretative analysis of the works, (4) the editing of the manuscripts and sheet music (5 ) interpretive suggestions the author of this work recorded in public recital (recorded in CD-DVD).Part of the results recorded on DVD points out that Glauco Velasquez has a particular style advanced to the historical-musical of the season.